Simultaneous Analysis: The Effect of Electricity Consumption on Human Development Index in ASEAN 5 - Suryanto - Suryanto; Irwan Trinugroho; Fitri Susilowati (Universitas Negeri Semarang, 2022)
A high per capita electricity consumption in developed countries is also correlated with high numbers on the human development index. Several studies show the relationship between the level of electricity consumption on economic growth and vice versa. This study aims to explore the relationship between electricity consumption, Human Development Index (HDI), and inflation to Gross Domestic Product (GDP) per Capita in ASEAN 5 countries. Using the simultaneous equation for the period 2012 to 2010 with the indirect least squares (ILS) analysis technique, it is found that electrical energy consumption has a positive effect on GDP per capita but HDI (Human Development Index) does not significantly affect GDP per Capita in ASEAN 5 countries. Meanwhile, the obtained inflation variable does not affect GDP per Capita. Then, we develop the second model and third model to test the impact on GDP per capita, electricity per capita, and HDI. The second model HDI as the dependent variable is influenced by the level of electricity consumption per capita and GDP per capita. This result proves that HDI is not influenced significantly by GDP per capita but is influenced by electricity consumption per capita. The third model shows empirical evidence that GDP per capita and HDI affect the level of electricity consumption. The policy implication is that electricity consumption will increase along with the increase in economic growth. The government must be able to increase supply to fulfill the rising electricity demand.